2023
DOI: 10.3390/ijms24032261
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Effects on Adipocyte Niche Stiffness and Cell Signaling

Abstract: Adipose tissue metabolism under hyperglycemia results in Type II diabetes (T2D). To better understand how the adipocytes function, we used a cell culture that was exposed to glycation by adding intermediate carbonyl products, which caused chemical cross-linking and led to the formation of advanced glycation end products (AGEs). The AGEs increased the cells and their niche stiffness and altered the rheological viscoelastic properties of the cultured cells leading to altered cell signaling. The AGEs formed conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The involvement of adipocytes in the internalization and metabolism of glucose led us to examine how the formation of AGEs can affect cellular activity and specifically the differentiation capacity of 3T3-L1 cells. As already discussed, we have previously reported that treating cell cultures with the carbonyl compounds MGO and GAD decreases the level of adipogenesis (LOA) (25). Here, we extended the study to changes in adipocyte morphology and specifically to effects on cellular area and LD size.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The involvement of adipocytes in the internalization and metabolism of glucose led us to examine how the formation of AGEs can affect cellular activity and specifically the differentiation capacity of 3T3-L1 cells. As already discussed, we have previously reported that treating cell cultures with the carbonyl compounds MGO and GAD decreases the level of adipogenesis (LOA) (25). Here, we extended the study to changes in adipocyte morphology and specifically to effects on cellular area and LD size.…”
Section: Resultsmentioning
confidence: 80%
“…We have previously reported an altered LOA in cells treated with MGO/GAD (25). This was extended here to an examination of the effects of the carbonyl compound on lipolysis ( The autophagy process was monitored by staining for LC3 II expression, a marker protein for autophagosome vesicles and provides the outcome as a puncta assay.…”
Section: Carbonyl Compounds Influence the Intracellular Degradation P...mentioning
confidence: 76%
See 2 more Smart Citations
“…Regardless of the direct impact on adipocytes, AGE formation in hyperglycemic conditions damages other components of adipose tissue. Recent studies on 3T3-L1 preadipocytes suggest that the accumulation of AGEs in the ECM, independently of the RAGE pathway, impairs adipocyte differentiation [ 36 ]. In addition, through ECM modification, AGEs have direct effects on cell niches and plasma membranes via loss of their plasticity and therefore induce alterations in cellular signaling and cytoskeletal organization.…”
Section: Influence Of the Rage Pathway On Adipose Tissue Activitymentioning
confidence: 99%